Chronic kidney disease unawareness and determinants using 1999–2014 National Health and Nutrition Examination Survey Data. (9th April 2021) - Florea, Ana; Jacobs, Elizabeth T; Harris, Robin B; Klimentidis, Yann C; Thajudeen, Bijin; Kohler, Lindsay N
Abstract: Background: Although chronic kidney disease (CKD) affects 15% of the United States (US) population, <10% of the US CKD population is aware of their disease. This is significant as untreated CKD can progress to end-stage renal disease which would require dialysis or transplantation. This study aimed to provide updated information regarding US CKD unawareness. Methods: Data from the 1999–2014 National Health and Nutrition Examination Survey (NHANES) were used ( n = 38 474); response rate > 70%. CKD self-report and lab-confirmed CKD were used to assess CKD unawareness. Adjusted logistic regression models examined association between unawareness and patient characteristics. Results: In individuals with lab-confirmed CKD ( n = 7137, 14.3%), 91.5% answered 'no' to self-report question; in those without CKD, 1.1% answered 'yes' to self-report question. In those with lab-confirmed CKD, in the adjusted models, increased age [odds ratio (ORs), 1.03 (95%CI, 1.02–1.04)] and female sex [OR, 1.37 (95%CI, 1.08–1.72)] were statistically significantly associated with greater odds of being unaware of CKD. Conclusion: These findings demonstrated high unawareness of disease status as there was a discrepancy between respondents' self-reported CKD diagnosis and lab-confirmed CKD. Older individuals and women may be more unaware of their CKD; these groups should be queried about reasons for increased unawareness.